1999
DOI: 10.1016/s0166-4328(98)00004-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of lateral septal vasopressin receptor blockade in spatial learning, social recognition, and anxiety-related behaviors in rats

Abstract: The role of lateral septal vasopressin (VP) in the modulation of spatial memory, social memory, and anxiety-related behavior was studied in adult, male Wistar rats. Animals were equipped with osmotic minipumps delivering the VP-antagonist d(CH2)5-DTyr(Et)VAVP (1 ng/0.5 vl per h) bilaterally into the lateral septum (LS). Subsequently, all rats were subjected to four behavioral tests. First, animals were tested in a spatial learning paradigm (Morris water maze; 12 trials), followed by the social recognition test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 51 publications
4
90
0
2
Order By: Relevance
“…The significantly reduced anxietylike behaviors observed in the V1aRKO subjects provide additional, nonpharmacological support for the role of V1aR in regulating anxiety behavior. Under the conditions used for testing, the WT subjects exhibited elevated levels of anxiety-like behavior relative to other reports (Everts and Koolhaas, 1999). The reasons for this are unclear but could be due to lux levels, time of day, and/or the general conditions in our mouse colony or testing rooms.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The significantly reduced anxietylike behaviors observed in the V1aRKO subjects provide additional, nonpharmacological support for the role of V1aR in regulating anxiety behavior. Under the conditions used for testing, the WT subjects exhibited elevated levels of anxiety-like behavior relative to other reports (Everts and Koolhaas, 1999). The reasons for this are unclear but could be due to lux levels, time of day, and/or the general conditions in our mouse colony or testing rooms.…”
Section: Discussionmentioning
confidence: 69%
“…Appenrodt et al (1998), reported a decrease in anxietyrelated behavior after central or peripheral AVP administration but no effect of an AVP antagonist, while Liebsch et al (1996) found no effect of AVP on anxiety behavior, but did find a decrease in anxiety-related behavior after treatment with a V1 receptor antagonist. A third group found that AVP receptor antagonism increased anxiety-like behavior (Liebsch et al, 1996;Appenrodt et al, 1998;Everts and Koolhaas, 1999). The V1bR has also been implicated in anxiety, and treatment with an orally active V1bR antagonist resulted in a decrease in anxiety-related behavior in rats (Griebel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown VP increases agonistic behavior in several rodent species, including hamsters and voles. [8][9][10][11] Furthermore, specific V1aR agonists and antagonists also affect aggression, 9,18,19 suggesting that the V1aR mediates some of these effects. We have now shown that V1b receptors must play a role in mediating VP's effects on aggression.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Administration of vasopressin V1a receptor (V1aR) agonists and antagonists affects both of these behaviors. 8,14,[17][18][19] Greater understanding of VP's and its receptors' functions in animal models may lead to improved clinical treatment for aggression. The recently cloned pituitary V1b receptor (V1bR; sometimes referred to as V3R) is also expressed in the brain, 20,21 suggesting a potential role in aggression and other behaviors.…”
Section: Introductionmentioning
confidence: 99%